A Pragmatic Analysis of Deixis and Reference on Taylor Swift Songs - Claurin Sahusilawane; Parjolo Aritonang; Orpa Penina Oraile; Rosina F. J. Lekawael (MATAI: International Journal of Language Education, 2023)
This research examines the pragmatic aspects of deixis and reference in song lyrics. Pragmatics is concerned with how speakers or writers convey meaning, and how listeners or readers interpret it. Deixis refers to linguistic elements that directly refer to the personal, temporal, or locational characteristics of the situation in which an utterance occurs. The study explores the different types of deixis, including person deixis, spatial deixis, temporal deixis, discourse deixis, and social deixis, and their role in establishing meaning and creating a connection between the songwriter and the audience. Reference, on the other hand, focuses on the identification of things in the world, with deixis serving as the mechanism for achieving reference. The analysis highlights the importance of context in determining the referents of deictic expressions and the impact of deixis and reference in conveying the songwriter's intended message. By understanding the pragmatic use of deixis and reference in song lyrics, researchers and readers can gain insights into the communicative strategies employed by songwriters and the ways in which meaning is constructed within the lyrics.